Tributary water depth and velocity remote monitoring system using Arduino and LoRa - Jasni, Ammar Azizi; Ahmad, Yasser Asrul; Gunawan, Teddy Surya; Yaacob, Mashkuri; Ismail, Nanang; Wasik, Abdul (IEEE, 2022)
Currently, monitoring tributary water depths and velocity is divided into two distinct setups, and the majority of data extraction is performed manually. This paper aims to develop a real-time remote monitoring system capable of measuring the depth and velocity of tributary water in real-time. The system measures and records the water flow speed using the YS-F201 Hall-effect water flow sensor and the water depth using the HC-SR04 ultrasonic sensor. The Arduino Uno R3 microcontroller is used to process raw data using a set of computational functions to generate final depth and velocity values. For remote monitoring and data communication, the LoRa SX1278 module is integrated with the microcontroller. At -102dBm, the LoRa modules detect a minimum RSSI. The ultrasonic sensor has a 97.72 % accuracy in measuring water depths up to 1.5 meters and a 98.19 % accuracy in measuring water velocity. The experimental results established the system's utility.